The impact of COVID-19 on 30-day mortality in patients with neck of femur fractures. (2020) - Archer, James E.; Kapoor, Siddhant; Piper, Danielle; Odeh, Abdulrahman
Abstract : Aims: The COVID-19 pandemic presents a significant threat to patients with neck of femur fractures. The 30-day mortality for these patients has gradually been reducing in the UK due to a multitude of inputs aimed at improving their outcomes. We provided an early assessment of 30-day mortality in neck of femur fracture patients who contracted COVID-19. Methods: We identified 18 patients who were admitted from three acute hospital sites who underwent an operation for a neck of femur fracture and were diagnosed with COVID-19 between 25 March and 25 April 2020. We collected information on their age, American Association of Anesthesiologists (ASA) grade, diagnosis, surgical procedure, complications, and 30-day mortality. Results: Our study identified 18 patients who were all diagnosed with a positive swab result during the postoperative period. Female patients made up two-thirds of the patient cohort and the mean age of patients was 82 years (55 to 101). In all, ten patients sustained intracapsular fractures with eight sustaining extracapsular fractures. The 30-day mortality in this group of patients was 22.2% as compared to 4% 30-day mortality in those without COVID-19. Conclusion: Our results show a 30-day mortality of 22.2%, which is higher than the national average provided by the 2019 National Hip Fracture Database report. However, while 30-day mortality has increased in those patients with COVID-19, this should not impact upon the provision of hip fracture surgery as it provides significant benefits to the patient such as pain relief and early mobilization. However, the information presented in this study should form an important part of the informed consent process for surgery. A multidisciplinary approach is crucial in ensuring optimal care for this complex patient group. Cite this article: Bone Joint Open 2020;1-7:326–329.